BNYVV-derived dsRNA confers resistance to rhizomania disease of sugar beet as evidenced by a novel transgenic hairy root approach - Pavli, Ourania I. (Springer Netherlands, 2010)
Agrobacterium rhizogenes-transformed sugar beet hairy roots, expressing dsRNA from the Beet necrotic yellow vein virus replicase gene, were used as a novel approach to assess the efficacy of three intron-hairpin constructs at conferring resistance to rhizomania disease. Genetically engineered roots were similar in morphology to wild type roots but were characterized by a profound abundancy, rapid growth rate and, in some cases, plagiotropic development. Upon challenge inoculation, seedlings showed a considerable delay in symptom development compared to untransformed or vector-transformed seedlings, expressing dsRNA from an unrelated source. The transgenic root system of almost all seedlings contained no or very low virus titer while the non-transformed aerial parts of the same plants were found infected, leading to the conclusion that the hairy roots studied were effectively protected against the virus. This readily applicable novel method forms a plausible approach to preliminarily evaluate transgenic rhizomania resistance before proceeding in transformation and whole plant regeneration of sugar beet, a tedious and time consuming process for such a recalcitrant crop species.